DAMPAK PUTUSAN MK TERHADAP HAK POLITIK MANTAN KORUPTOR DALAM PENCALONAN ANGGOTA LEGISLATIF 2024: The Impact of the Constitutional Court Decision on the Political Rights of Former Corruptors in the Candidacy for Legislative Members in 2024 - Aurigae Bee Hendra; Radian Syam (Faculty of Law, Universitas Trisakti, 2025)
In a democratic country, elections play a crucial role in shaping a power system based on the sovereignty of the people. The Election Law regulates the requirements for candidacy for the positions of President, Vice President, and legislative members. However, currently, many legislative candidates do not adhere to the specified criteria. The identification problem revolves around the rights of former corrupt convicts before and after Constitutional Court Decision Number 87/PUU-XX/2022, as well as the implications and consequences following the decision, which altered one of the conditions for candidacy as a legislator. The research method employed is a normative and descriptive study, utilizing secondary data as the source of information. This data is qualitatively analyzed, and conclusions are drawn deductively. The result research and conclusion indicate that Constitutional Court Decision Number 87/PUU-XX/2022 has led to changes in the eligibility criteria for legislative candidates, particularly for former convicts, who are now required to wait for 5 years after their release before being eligible to run for election again.